Odpowiedzi

2010-03-17T17:45:39+01:00
6 ( x - 4 ) = jedna piąta ( 10 x - 2 )
6x-24=2x-2/5
4x=-2/5+24
4x=23 3/5 /4
x=5 9/10

2 ( x + 3 ) - 2 ( 3 x - 7 ) = 0
2x+6-6x+14=0
-4x=-20 /-4
x=5



2 x + 4 = 6 x - 9
______ ______
2 3

(2x+4)/2=(6x-9)/3 /*6
3(2x+4)=2(6x-9)
6x+12=12x-18
-6x=-30 /-6
x=5
2010-03-17T17:46:41+01:00
6 ( x - 4 ) = jedna piąta ( 10 x - 2 )
6(x-4)=1\5(10x-2)
6x-24=0,20(10x-2)
6x-24= 2x-0,4
6x-2x= 0,4-24
4x= 23,6/:4
x=-5,9

2 ( x + 3 ) - 2 ( 3 x - 7 ) = 0
2x+6-6x-14=0
2x-6x=14-6
-4x=8/:
x=-2

2 x + 4 = 6 x - 9
______ ______
2 3
(skracamy z pierwszego działnia dwujki i zostaje na 1x+4 a w drogim 3 skracamy i zostanie nam 6x-3)
x+4=6x-3
-6x-x=-3-4
-7x=7\:7
x=1
2010-03-17T17:56:11+01:00

6 ( x - 4 ) = jedna piąta ( 10 x - 2 )
6x-4=2x-0,4
6x-2x=4-0,4
4x=3,6 /4
x=0,9

2 ( x + 3 ) - 2 ( 3 x - 7 ) = 0
2x+3+6-6x+14=0
2x-6x=0+3+6+14
-4x=23
x=-5,75

2 x + 4 = 6 x - 9 2x-6x=-4-9 -4x=-13 x=3,25
______ ______ =________________ =___________=___________=
2 3 23 23 23
325/100:23=325/100*1/23=13/4*1/23=13/92